1997
DOI: 10.1074/jbc.272.38.23653
|View full text |Cite
|
Sign up to set email alerts
|

Role of Serine/Threonine Protein Phosphatases in Insulin Regulation of Na+/K+-ATPase Activity in Cultured Rat Skeletal Muscle Cells

Abstract: In this study, we examined the potential role of serine/ threonine protein phosphatase-1 (PP-1) and PP-2A in the mechanism of Na

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 34 publications
2
27
2
Order By: Relevance
“…Wortmannin also abolishes insulin-induced Na,K-ATPase activity in skeletal muscle cells (31) and insulin-induced plasma membrane insertion of Na,K-ATPase ␣ 1 proteins in skeletal muscle (32) and human embryonic kidney-293 cells (33). These effects of PI3K inhibitors on Na,K-ATPase activity or translocation indicate that PI3K is involved in the Na,K-ATPase regulation of activity and translocation to the cell surface in several cell types.…”
Section: Discussionmentioning
confidence: 91%
“…Wortmannin also abolishes insulin-induced Na,K-ATPase activity in skeletal muscle cells (31) and insulin-induced plasma membrane insertion of Na,K-ATPase ␣ 1 proteins in skeletal muscle (32) and human embryonic kidney-293 cells (33). These effects of PI3K inhibitors on Na,K-ATPase activity or translocation indicate that PI3K is involved in the Na,K-ATPase regulation of activity and translocation to the cell surface in several cell types.…”
Section: Discussionmentioning
confidence: 91%
“…2A shows that pre-incubation of ATII cells with genistein, a broad tyrosine-kinase inhibitor, completely prevented insulin-induced Na + /K + -ATPase recruitment without affecting the basal levels. Previous studies reported the participation of the PI3K-signaling system in the activation of Na + /K + -ATPase in fibroblast and kidney epithelial cells (Deachapunya et al, 1999;Ragolia et al, 1997;Sweeney et al, 2001). Incubation with 100 nM wortmannin or LY 294002, two PI3K inhibitors, markedly prevented insulin-induced Na + /K + -ATPase translocation (Fig.…”
Section: Atpase Activitymentioning
confidence: 99%
“…Myotubes were serum-starved 18 h prior to the experiment. Differentiated L6 myotubes express only the ␣ 1 -subunit isoform of Na ϩ ,K ϩ -ATPase (30). AMPK␣ Knock-out Cells-Primary muscle cell cultures were derived from gastrocnemius and tibialis anterior muscles of 4-week-old wild-type and AMPK␣1…”
Section: Methodsmentioning
confidence: 99%